2010
DOI: 10.1179/136217110x12785889549462
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir spot welding of AA 1050 Al alloy and hot stamped boron steel (22MnB5)

Abstract: The present study investigates the effect of joining parameters on the microstructural and mechanical characteristics of dissimilar friction stir spot welding (FSSW) between AA 1050 Al and 22MnB5 hot stamped boron steel. Mechanical performance has been evaluated by shear and microhardness testing. Optical microscopy has been used to investigate the microstructure generated in the different FSSW regions. A macrostructural examination has revealed the creation of mechanical interlocking in the Al steel connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…The welding flash is not commonly considered in the research of FSSW. Previous work by Da Silva et al showed the mechanical importance of welding flash by indicating that the formation of a larger secondary flash improved the mechanical interlocking between lower and upper sheet with higher tool plunge depth .…”
Section: Introductionmentioning
confidence: 95%
“…The welding flash is not commonly considered in the research of FSSW. Previous work by Da Silva et al showed the mechanical importance of welding flash by indicating that the formation of a larger secondary flash improved the mechanical interlocking between lower and upper sheet with higher tool plunge depth .…”
Section: Introductionmentioning
confidence: 95%
“…Larger tool offset means larger portion of the tool pin submerged in aluminum. Considering the severe frictional conditions associated with stirring steel, refractory materials such as tungsten carbide [20][21][22][23], tungsten-rhenium [24], Si 3 N 4 [25], and polycrystalline cubic boron nitride (PCBN) [26][27][28] are required as acceptable tool material candidates. In this study, tungsten carbide with a 10 % cobalt content was selected for its combination of good wear resistance and much lower cost compared with PCBN.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional friction stir spot welding (FSSW) is a relatively new solid-state joining technology, which is a natural alternative to fusion welding due to that it avoids the problems of solidification and liquation cracking [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Mazda has used conventional FSSW to join Al alloy to coated steels in aluminum trunk lid [27], acceptable weld strength was achieved although keyhole significantly decreased effective bonded area [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%